Sistem Kendali Cerdas Penggunaan Daya Listrik Menggunakan Metode Eliminasi Nilai Tertinggi Berbasis IoT - Mochamad Susantok; Noptin Harpawi; Muhammad Diono (Jurnal Elektro dan Mesin Terapan, 2022)
The use of electrical equipment that exceeds the maximum power limit of the Miniature Circuit Breaker (MCB) determined by PLN so that there is a power outage is a problem for users of the household sector.The amount of initial power consumption when the electrical equipment is turned on again becomes a burden for the household sector. This can be prevented, one of which is by adjusting the electrical power load so that it does not exceed the threshold limit in the MCB. The intelligent control system in this study uses the IoT NodeMCU ESP8266 device as a sensor node that can measure the power used from electrical equipment connected to the sensor node. One of the sensor nodes calculates the total measured power of all active sensor nodes and determines the action for an overload condition. The overload condition is met if the total rated power exceeds the specified maximum power threshold. The action of this condition selects the highest power system at each sensor node and disconnects the electric current at the selected sensor node so that the electrical equipment with the highest power is off and the total power is corrected below the threshold limit. This algorithm is used to prevent disconnection in the MCB due to exceeding the electrical load or the maximum power allowed according to the provisions by PLN. The average power measurement accuracy at the sensor node is 85.9% or with a % error of 14.1% and the highest power elimination algorithm manages to keep the total power load below a predetermined threshold. As a result, electrical equipment with the highest power will always be compensated when conditions touch the maximum power threshold.